Endogenous hydrogen peroxide in the hypothalamic paraventricular nucleus regulates sympathetic nerve activity responses to L-glutamate - Cardoso, Leonardo M.; Colombari, Eduardo [UNESP]; Toney, Glenn M. (Amer Physiological Soc, 2012)
Cardoso LM, Colombari E, Toney GM. Endogenous hydrogen peroxide in the hypothalamic paraventricular nucleus regulates sympathetic nerve activity responses to L-glutamate. J Appl Physiol 113: 1423-1431, 2012. First published September 13, 2012; doi:10.1152/japplphysiol.00912.2012.-The hypothalamic paraventricular nucleus (PVN) is important for maintenance of sympathetic nerve activity (SNA) and cardiovascular function. PVN-mediated increases of SNA often involve the excitatory amino acid L-glutamate (L-glu), whose actions can be positively and negatively modulated by a variety of factors, including reactive oxygen species. Here, we determined modulatory effects of the highly diffusible reactive oxygen species hydrogen peroxide (H2O2) on responses to PVN L-glu. Renal SNA (RSNA), arterial blood pressure, and heart rate were recorded in anesthetized rats. L-Glu (0.2 nmol in 100 nl) microinjected unilaterally into PVN increased RSNA (P < 0.05), without affecting mean arterial blood pressure or heart rate. Effects of endogenously generated H2O2 were determined by comparing responses to PVN L-glu before and after PVN injection of the catalase inhibitor 3-amino-1,2,4-triazole (ATZ; 100 nmol/200 nl, n = 5). ATZ alone was without effect on recorded variables, but attenuated the increase of RSNA elicited by PVN L-glu (P < 0.05). PVN injection of exogenous H2O2 (5 nmol in 100 nl, n = 4) and vehicle (artificial cerebrospinal fluid) were without affect, but H2O2, like ATZ, attenuated the increase of RSNA to PVN L-glu (P < 0.05). Tonic effects of endogenous H2O2 were determined by PVN injection of polyethylene glycol-catalase (1.0 IU in 200 nl, n = 5). Whereas polyethylene glycol-catalase alone was without effect, increases of RSNA to subsequent PVN injection of L-glu were increased (P < 0.05). From these data, we conclude that PVN H2O2 tonically, but submaximally, suppresses RSNA responses to L-glu, supporting the idea that a change of H2O2 availability within PVN could influence SNA regulation under physiological and/or disease conditions.
Keywords: glutamatergic transmission; arterial blood pressure; reactive oxygen species; catalase; superoxide dismutase